2021
DOI: 10.3390/ijms221910677
|View full text |Cite
|
Sign up to set email alerts
|

The Distinct Properties of the Consecutive Disordered Regions Inside or Outside Protein Domains and Their Functional Significance

Abstract: The consecutive disordered regions (CDRs) are the basis for the formation of intrinsically disordered proteins, which contribute to various biological functions and increasing organism complexity. Previous studies have revealed that CDRs may be present inside or outside protein domains, but a comprehensive analysis of the property differences between these two types of CDRs and the proteins containing them is lacking. In this study, we investigated this issue from three viewpoints. Firstly, we found that in-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The hydrophobicity of the tested peptides was indicated using the GRAVY value. Peptides with negative GRAVY values are hydrophilic, while the positive values are hydrophobic [43]. The hydrophilic compound is considered more favourable in drug design to facilitate the hydrophilic nature of the cell and support good compound absorbance.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrophobicity of the tested peptides was indicated using the GRAVY value. Peptides with negative GRAVY values are hydrophilic, while the positive values are hydrophobic [43]. The hydrophilic compound is considered more favourable in drug design to facilitate the hydrophilic nature of the cell and support good compound absorbance.…”
Section: Resultsmentioning
confidence: 99%
“…The instability index serves as a valuable metric for assessing the intrinsic stability of a protein from its amino acid composition. 49 A set of 16 altered proteins have an instability index surpassing 40, indicative of their instability per se. The aliphatic index of a protein is described as the relative volume occupied by aliphatic side chains of amino acids such as alanine, valine, isoleucine, and leucine.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Also, in terms of solubility, it was predicted as a soluble molecule and it was also shown that it has a high negative GRAVY. A negative GRAVY value indicates the hydrophilicity of a molecule, and therefore our structure was recognized as a generally hydrophilic molecule 50,51 .…”
Section: Discussionmentioning
confidence: 99%